NAGEKEO WOMEN'S CULTURAL STRUGGLE AS A FLORES SUB-CULTURE AGAINST THE FLOW OF CIVILIZATION'S PROGRESS - Daniel Susilo; Teguh Dwi Putranto; Maria Theresia Lestari Mola Neu; Charles Julian Santos Navarro (Universitas Bunda Mulia, 2020)
ABSTRACT HobaPojo is a traditional cloth from the Nagekeo district that is commonly used by Nagekeo women. However, the development of fashion with other motive trends made hobapojo less prestige and began to be abandoned. This qualitative study uses case studies, in-depth interviews with triangulation methods to achieve research credibility. Data was found that the hobapojo cloth was traditionally intended for Nagekeo women. The meaning contained in the cloth covers the entire life cycle to the death of Nagekeo woman. Hobapojo must be used in a variety of traditional events, like clothing, blankets, dance costumes, surrender at the wedding, and cut teeth until the luggage when he died. Hobapojo is also a handicraft product for Nagekeo women to support their lives and to drive the family economy. There are rules in the use of fabrics, and each motif represents the characteristics and thinking skills of the weavers as a form of existence and effort to preserve culture. Keywords; Culture; HobaPojo; Cultural Communication. ABSTRAK HobaPojo adalah kain tradisional dari distrik Nagekeo yang biasa digunakan oleh wanita Nagekeo. Namun, perkembangan mode dengan tren motif lainnya membuat hobapojo kurang gengsi dan mulai ditinggalkan. Penelitian kualitatif ini menggunakan studi kasus, wawancara mendalam dengan metode triangulasi untuk mencapai kredibilitas penelitian. Data ditemukan bahwa kain hobapojo secara tradisional ditujukan untuk wanita Nagekeo. Makna yang terkandung dalam kain mencakup seluruh siklus hidup sampai kematian wanita Nagekeo. Hobapojo harus digunakan dalam berbagai acara tradisional, seperti pakaian, selimut, kostum tari, pasrah di pesta pernikahan, potong gigi sampai koper ketika ia meninggal. Hobapojo juga merupakan produk kerajinan tangan untuk wanita Nagekeo untuk mendukung kehidupan mereka dan untuk mendorong ekonomi keluarga. Ada aturan dalam penggunaan kain, dan masing-masing motif mewakili karakteristik dan keterampilan berpikir para penenun sebagai bentuk keberadaan dan upaya untuk melestarikan budaya. Kata kunci; Budaya; HobaPojo; Komunikasi Budaya.